The Effect of Brand Awareness, Brand Image and Trust on Consumer's Repurchasing Interest (Study at PT Astra International Isuzu, Warung Buncit Branch, South Jakarta) - Utama, Andyan Pradipta; Ambarwati, Aprilia Ningrum (Budapest International Research and Critics University, 2022)
This study is to analyze the effect of brand awareness, brand image and trust on consumer repurchase intention of PT Astra International Isuzu Warung Buncit Branch. The object of this research is Isuzu truck customers who have bought at least 2 times. Determination of sample size using the formula Hair et al., so that the sample used is 150 people. The research method used is quantitative research and the data analysis method used is PLS (Partial Least Square) technique through SmartPLS 3.2.9 software, using survey method, with research instrument is a questionnaire. This study proves that brand awareness has a negative effect with a value of -0.147 and is not significant on consumer repurchase interest with a T- statistic value of 1.283.